(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
The delinquent area, as the basic concept of ecological theory in criminology, is a natural area that exists in the city, such as ghettos, which ariseс in the process of urbanization and development and is significant for its characteristic patterns of antisocial behavior. The concept of a delinquent area comes directly from the concept of a natural area in environmental theory, and the epithet “delinquent” refers to the dominant pattern of behavior expressed by a large number of residents in that area. The theory of crime prevention, through the appearance of the environment, is based on the simple idea that the crime partly originates from the circumstances that are in the physical environment. Some of the research in the field of victimology was devoted to examining the impact that a ‘satisfactory’ neighborhood would have on victimization and social participation of the population, and ultimately on the experience of security in the neighborhood. It is emphasized that such an approach presupposes systematic testing of the relative importance of victimization, the importance of the quality of the neighborhood environment and social integration within society in preventing the fear of crime. The observation of child abuse in the delinquent area, related to the unity of the environment-sociology-culture model, is focused on the experience of stress in society, which is considered to be the primary cause of victimization. This category of abuse includes the following causes: stress environment model; social learning model; socio-psychological model and the model of psychosocial systems.